A Comparative Kinetic Study of Saponification of Industrially Important Esters - Madhava Rao, B.; Kulkarni, M.J.; Qureshi, Anjum (Asian Journal of Chemistry, 2010)
Kinetics of saponification of seven structurally related and industrially important diesters have been investigated. Time Ratio method and Swain's standard data for series first order reactions have been utilised for the evaluation of rate data and thermodynamic parameters viz, ΔE≠, –ΔH≠, ΔG≠ , ΔS≠ and log A for both the steps which involve the competitive and consecutive saponification reactions which also indicate that the first step of saponification process is quite faster than the second step and furthermore the stearates are more saponifiable than laurates and oleosterate in 72% alcohol-water moiety and in general these processes are much faster in acetone-water system than in alcohol-water.